The Effectiveness of Edmodo as Online Learning Platform for High School Students - Alexander, Jonathan (IALLTEACH (Issues In Applied Linguistics & Language Teaching), 2021)
Technology is used almost in all fields, including education. Applying technology in education can be done through a model called online learning. However, not all institutions have applied online learning for their students. Tenuous relationship between students and teachers, lack of face-to-face meeting, and undisciplined students are problems faced in conventional method. This research aims to conduct an online learning using Edmodo for 71 students at grade X in two classes in Yos Sudarso High School. This research utilized quantitative and qualitative experimental method. Observation and questionnaires were data collection techniques used for this research. The result proved that Edmodo is really best to be applied for online learning because it is easy to use. It also gained students’ satisfaction during the implementation. However, some problems were also encountered such as students’ lack responsibilities in learning, missed notification, and more assignments. This research also provides suggestions for further related research.